Analysis of Corporate Social Responsibility (CSR) Implementation in PT. Saraswanti Anugerah Makmur Tbk (Fertilizer Supplier) - Riky Aulia Rachman Marpaung; Dicky Effendy; Rizsa Nabillah Lesmana; Khairani Alawiyah Matondang; Noni Rozaini (Outline Publisher, 2022)
The purpose of this study is to analyze the CSR Implementation carried out by PT. Saraswanti Anugerah Makmur Tbk (Fertilizer Supplier). Methods of research conducted using qualitative data by conducting interviews with the company and developed with literature, reading books and literature by ilimiah related to this research. The results of the research obtained that the implementation of CSR carried out by parties PT. Saraswanti Anugerah Makmur TBK is in accordance with the applicable regulations in indonesia because of PT. already act ethically, operate legally and contribute to improve the quality of life of employees and their families, local communities, and wider community with the implementation of this CSR by the company.